THE EFFECT OF LOCAL GOVERNMENT EXPENDITURE ON DEVELOPMENT INEQUALITY WITHIN AND OUTSIDE JAVA ISLAND - Margaretta; Iranto, Dicky; Nikensari, Sri Indah (Faculty of Economics and Business, Universitas Negeri Jakarta, 2024)
This study aims to determine the effect of local government spending on infrastructure, education and health sectors on development inequality in Java and the Eastern Region. This research uses a quantitative approach, using panel data consisting of 18 provinces over a period of five years (2017-2021). The data analysis involves three main steps: (1) testing the model using the Chow test, Hausman test, and Lagrange multiplier test; (2) conducting classical assumption tests including normality, multicollinearity, and heteroscedasticity tests; and (3) performing hypothesis testing using t-test, F-test, and determination coefficient (R²) test. Research results shows that spending in the infrastructure sector has a negative impact on development gaps. Every 1% increase in local government spending on infrastructure can reduce the development gap by 1%. On the other hand, spending in the education sector has a positive and significant impact, where a 1% increase in spending will increase the development gap by 1%. Expenditures in the health sector do not have a significant impact on the development gap between Java Island and the Eastern Region.